2018
DOI: 10.1002/elps.201800192
|View full text |Cite
|
Sign up to set email alerts
|

Combined detection of AC‐electrokinetic effects: Experiments with three‐axial chicken red blood cells

Abstract: Dielectrophoresis (DEP), electrorotation (ROT), and electro-orientation were used for the dielectric spectroscopy of nucleated three-axial chicken red blood cells (CRBCs). Because the different AC-electrokinetic effects are not mutually independent, their DEP and ROT spectra were combined in ranges separated by the reorientation of the CRBCs in the inhomogeneous linear DEP and circular ROT fields. This behavior can be qualitatively described by a single-shell ellipsoidal model. Whereas in linear fields, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, there are at least two arguments against this assumption. First, in 3D, the 2D-pointed electrode corresponds to a 1 m vertical blade, and second, a voxel ratio of electrode to object of 1:39 ( Figure 1 ) is similar to the size ratio of 110 nm-thick glass-chip electrodes and 4 µm cells [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there are at least two arguments against this assumption. First, in 3D, the 2D-pointed electrode corresponds to a 1 m vertical blade, and second, a voxel ratio of electrode to object of 1:39 ( Figure 1 ) is similar to the size ratio of 110 nm-thick glass-chip electrodes and 4 µm cells [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Frusawa et al 171 reported frequency-modulated wave DEP for pDEPand nDEP-based manipulation of RBCs and vesicles in the range near the crossover frequencies. Gimsa et al 172 used single-shell ellipsoidal and triple-shell spherical theoretical models for studying the DEP, electro-rotation, and electroorientation characteristics of chicken RBCs. The authors concluded that the single-shell ellipsoidal model qualitatively reflects the experimentally observed electrokinetic properties of chicken RBCs.…”
Section: ■ Technical Realization Platforms For Depmentioning
confidence: 99%
“…and Gimsa et al. . The interaction of nonuniform electric field by the smeared spatial charges can drive an effective medium flow, and the induced ACET pumping force depends on the temperature and field gradients, as well as on the frequency of AC electric field.…”
Section: Theory and Simulationmentioning
confidence: 99%
“…Generally, the ACEO effect diminishes at the high‐conductivity medium (σ>0.085 S/m) and high‐frequency AC signal (f>100 kHz) . The main reasons are that the electric double layer can be neglected because of the capacitive bridging at high frequency , and the thickness of double layer decreases as the concentration of ions increases in the fluid , making ACEO ineffective with high conductivity. The pumping capacity of a spiral ACET micropump can be evaluated by the average value of the horizontal fluidic velocity component u at the periodic outlet cross‐section, written as 0trueua=Sudydz/πfalse(Dh/2false)2.…”
Section: Theory and Simulationmentioning
confidence: 99%